Practical Preparation of (4R,5R,E)-methyl 5-(tert-butyldimethylsilyloxy)-4-hydroxyhepta-2,6-dienoate - Yudhi Dwi Kurniawan; Duen-Ren Hou; Rurini Retnowati (Chemistry Department, The University of Brawijaya, 2014)
This study is aimed to improve the preparation of uselful synthetic block (4R,5R,E)-methyl 5-(tert-butyldimethylsilyloxy)-4-hydroxyhepta-2,6-dienoate (1). This intermediate was used in the synthesis of (+)-Cladospolide D. The strategy developed by Voigtritter et al. was adopted to exploit the acceleration effect of copper (I) iodide. This compound was prepared from D-mannitol-derived dienediol (2) coupled with methyl acrylate through olefin cross-metathesis reaction in various conditions. It was found that performing the reaction in the presence of 3 mol% of CuI in refluxing diethyl ether gave the product up to 75% of yield with lower catalyst loading, i.e.: 2 mol%.